The Effect of GnRH on Reproductive Performance and Progesterone Hormone Levels in Buffalo in West Sumatera - Tinda Afriani; Ferdinal Rahim; Mangku Mundana; Arif Rahmat; Jaswandi; Anna Farhana (Politeknik Pembangunan Pertanian Manokwari, 2020)
The administration of hormone GnRH will affect the reproductive organs and can improve the reproductive performance of buffalo. The decrease of the buffalo population is caused by various factors including genetic and environmental factors. The development of buffaloes is relatively slow because the reproduction rate of buffaloes is lower than that of cattle, besides that it is also difficult to detect estrus, the pregnancy period is relatively long and longer calving rate. This study aims to determine the best dose of GnRH on the swamp buffalo producing of dadih in Indonesia. The materials used were 16 swamp buffalo. A completely randomized design was used in this study. Buffalo is synchronized with the injection of 5 ml of GnRH hormone n on the first and 11th day, on the 10th to 12th day all donor buffaloes are injected with GnRH. Four different doses of GnRH (200, 225, 250 and 275 ml/buffalo) and each treatment was replicated five times. The speed of estrus and estrus length were the measured variables. The results showed that the doses of GnRH significantly (P<0.05) increase of estrus speed and estrus length. Progesterone levels have increased significantly starting from before treatment until after treatment with GnRH. It is concluded that the best GnRH doses for estrus synchronization in the swamp buffalo producing of dadih was 2. 25 ml/buffalo with estrus speed 18.2 h and estrus length 18 h.